Conductas negativas que manifiestan los estudiantes de la escuela de Trabajo Social en los diferentes roles de la vida - Pineda Ruiz, Luz Verónica (2017)
The present investigation was carried out with the purpose of identifying theexistence of negative attitudes in the students of the School of Social Work -National University of Trujillo from 2014 to 2016. In order to be able to approachand to know about this problem, I placed myself in classroomsof students of theSchool of Social Work at the National University of Trujillo. In this way, supportnetworks were established that enabled the investigation, which allowedcomparing the level or degree of existence of negative attitudes in students andidentifying some of these. I also had the support of a survey already carried out byProf. Ibáñez Pantoja Josefina in the year 2014 since it was the beginning of myinterest in the research topic, mainly due to thenonexistenceof diagnosesorintervention models to solve or provide alternative solutions to this academicproblem. This research has been based on a methodological approach of quantitative-qualitative and comparative type. The sample population consisted of 800students of I, III, V, VII and IX cycle of the School of Social Work-UNT. In which ithas been possible to find that some of them have negative attitudes. With regardto the topic that summons us in the thesis, we can say that there is a lowknowledge of the subject of negative attitudes in the students of the School ofSocial Work, the few investigations that have been done on this subject, agree thatthis topic affects Many more people than those who recognize it, which shows usthe need to study it more in depth, because it is an emerging problem, in such away to know what their real dimensions. Based on these findings, in the present study we seek to get closer to students ofthe School of Social Work - UNT who present negative attitudes throughcharacterizing the socio-academic situation and the types of negative attitudesthey show. To what it points, it is to improve in the future the actions that areundertaken with this academic group. For this, the study of this problem isorganized in three chapters. In chapter I the reality is revealed in which the problem under study unfolds, as well as the antecedents of previous researches,the definition of the variables to study, under the approach of the problem, thehypotheses and the objectives On which the research is based, in the same waythe theoretical approaches used in the intervention with the students of the Schoolof Social Work are developed. CHAPTER II develops the methodology used in the present research, whichpresents the population, sample, methods, type of research, research design,procedures, techniques, instruments and validation of the latter. Later in CHAPTER III, this chapter is divided into four parts; In the first three parts,the results obtained from the questionnaire that was applied in the years2014,2015 and 2016 are shown, the questionnaire was applied taking into accountthe most negative attitudes in students such as: critic, condemnation, complaining,I only speak of what interests me, I do not listen, I impose an idea, I am indifferentand I am presumed, that affects in some way or another the roles of Student,Partner and Social. In the last part, the comparative picture of the results of thethree years of research is shown, which shows that the most affected role of life isSocialFinally, in chapter IV the analysis and discussion of the results are developed, aswell as the conclusions that were reached in this investigation and in turn somerecommendations are made both for the development of prevention actions andfor the development of future Research on the subject.